BRAFV600E Expression in Thyrocytes Causes Recruitment of Immunosuppressive STABILIN-1 Macrophages - Spourquet Catherine; Delcorte Ophélie; Lemoine Pascale; Dauguet Nicolas; Loriot Axelle; Achouri Younes; Hollmén Maija; Jalkanen Sirpa; Huaux Francois; Lucas Sophie; Meerkeeck Pierre Van; Knauf Jeffrey A; et al. (MDPI, 2022)
Papillary thyroid carcinoma (PTC) is the most frequent histological subtype of thyroid cancers (TC), and BRAFV600E genetic alteration is found in 60% of this endocrine cancer. This oncogene is associated with poor prognosis, resistance to radioiodine therapy, and tumor progression. Histological follow-up by anatomo-pathologists revealed that two-thirds of surgically-removed thyroids do not present malignant lesions. Thus, continued fundamental research into the molecular mechanisms of TC downstream of BRAFV600E remains central to better understanding the clinical behavior of these tumors. To study PTC, we used a mouse model in which expression of BRAFV600E was specifically switched on in thyrocytes by doxycycline administration. Upon daily intraperitoneal doxycycline injection, thyroid tissue rapidly acquired histological features mimicking human PTC. Transcriptomic analysis revealed major changes in immune signaling pathways upon BRAFV600E induction. Multiplex immunofluorescence confirmed the abundant recruitment of macrophages, among which a population of LYVE-1+/CD206+/STABILIN-1+ was dramatically increased. By genetically inactivating the gene coding for the scavenger receptor STABILIN-1, we showed an increase of CD8+ T cells in this in situ BRAFV600E-dependent TC. Lastly, we demonstrated the presence of CD206+/STABILIN-1+ macrophages in human thyroid pathologies. Altogether, we revealed the recruitment of immunosuppressive STABILIN-1 macrophages in a PTC mouse model and the interest to further study this macrophage subpopulation in human thyroid tissues.